Philippine English as a linguistic variety: A review of its features and sociolinguistic attitudes - Patrick Carlos D. Famanily; Famanily Rosemaie A. Capili; Joseree Ann L. Ferrer; Kenneth Cole S. Lacsina; Marilou D. Licup; Aileen Joy C. Sibal (Journal of Education, Social & Communication Studies, 2026)
This systematic review examines the linguistic and sociolinguistic characteristics of Philippine English (PhE) based on studies published from 2019 to 2026. Guided by research questions focusing on the phonological, lexical-semantic, and grammatical-syntactic features of PhE, as well as its sociolinguistic attitudes and functional roles in education, communication, and media, the study reviewed fifteen scholarly articles from credible academic databases and repositories. Findings reveal that PhE has developed into a legitimate and systematic variety of English shaped by local linguistic and cultural influences. Phonological studies identified recurring consonant substitutions, vowel mergers, and lectal variations influenced by regional and proficiency differences. Lexical-semantic features demonstrated linguistic creativity through borrowing, blending, clipping, compounding, and semantic shifts, particularly in digital communication contexts. Grammatical-syntactic analyses also revealed flexible subject–verb agreement, simplified tense marking, and localized sentence structures that reflect communicative adaptation rather than linguistic deficiency. Sociolinguistically, PhE is increasingly recognized as a marker of Filipino identity and communicative accessibility; however, native-speaker norms continue to dominate formal academic settings. The findings affirm that PhE is an evolving, rule-governed, and culturally grounded variety whose acceptance continues to expand across different social domains in the Philippines.